Cloud occurrences and cloud radiative effects (CREs) from CERES‐CALIPSO‐CloudSat‐MODIS (CCCM) and CloudSat radar‐lidar (RL) products. Issue 16 (31st August 2017) - Ham, Seung‐Hee; Kato, Seiji; Rose, Fred G.; Winker, David; L'Ecuyer, Tristan; Mace, Gerald G.; Painemal, David; Sun‐Mack, Sunny; Chen, Yan; Miller, Walter F.
Abstract: Two kinds of cloud products obtained from Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO), CloudSat, and Moderate Resolution Imaging Spectroradiometer (MODIS) are compared and analyzed in this study: Clouds and the Earth's Radiant Energy System (CERES)‐CALIPSO‐CloudSat‐MODIS (CCCM) product and CloudSat radar‐lidar products such as GEOPROF‐LIDAR and FLXHR‐LIDAR. Compared to GEOPROF‐LIDAR, low‐level (<1 km) cloud occurrences in CCCM are larger over tropical oceans because the CCCM algorithm uses a more relaxed threshold of cloud‐aerosol discrimination score for CALIPSO Vertical Feature Mask product. In contrast, midlevel (1–8 km) cloud occurrences in GEOPROF‐LIDAR are larger than CCCM at high latitudes (>40°). The difference occurs when hydrometeors are detected by CALIPSO lidar but are undetected by CloudSat radar. In the comparison of cloud radiative effects (CREs), global mean differences between CCCM and FLXHR‐LIDAR are mostly smaller than 5 W m −2, while noticeable regional differences are found. For example, CCCM shortwave (SW) and longwave (LW) CREs are larger than FXLHR‐LIDAR along the west coasts of Africa and America because the GEOPROF‐LIDAR algorithm misses shallow marine boundary layer clouds. In addition, FLXHR‐LIDAR SW CREs are larger than the CCCM counterpart over tropical oceans away from the west coasts of America. Over midlatitude storm‐track regions, CCCM SW and LW CREs are larger than the FLXHR‐LIDAR counterpart. Key Points: Both CCCM and CloudSat radar‐lidar (RL) algorithms combine cloud information measured by CALIPSO, CloudSat, and MODIS Different occurrences in low‐level clouds over tropics and midlevel clouds over high latitudes are due to different cloud thresholds Different CREs over the west coasts of continents, tropical oceans, and storm tracks are due to different cloud merging approaches